THE LINGUISTIC REPRESENTATION OF MOLUCCAS RIOTS IN AMBON’S LOCAL NEWSPAPER (SIWALIMA) - Michele Hitijahubessy; Nurul Chojimah; Esti Junining (Kadera Bahasa, 2019)
Riots in Moluccas were one of the biggest conflicts in Indonesia that occurred in 2000-2002, no wonder the incident was a concern of many parties, especially the mass media. However, the mass media is also not free from bias because there are ideologies that can affect the content of the news. For this reason, researchers conducted a study on the representation of the Moluccas riots in Siwalima. The focus of this research is on  problem of the study, how was the linguistic representation of the Moluccas riots in Siwalima?the objective of the study is to investigate the linguistic representation of Moluccas riots in Siwalima.This study used a qualitative method with Fairclough's (1995) model of Critical Discourse Analysis to help on the process of data analysis. The data used was linguistic representation of Moluccas riots in Siwalima. The researchers found that the linguistic representation of the Moluccas riots in Siwalima highlights more about the incompetence of the government and the military in dealing with the conflict. Hence, the military was considered to have favored only one particular group, even participated in extending the conflict and making native Moluccan victims of the conflict. The condition of Moluccas at that time was also represented as a gloomy event.